Migraine and sleep apnea, insomnia, and sleep patterns in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) - Vgontzas, Angeliki; Mittleman, Murray A.; Castro‐Diehl, Cecilia; Isasi, Carmen R.; Lipton, Richard B.; Patel, Sanjay R.; Ramos, Alberto; Sotres‐Alvarez, Daniela; Agudelo, Christian; Daviglus, Martha L.; Zee, Phyllis C.; Redline, Susan; et al. (Headache, 2025)
Objective To quantify the prevalence of migraine and examine its association with sleep disorders, patterns, and symptoms in adults in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We hypothesized that migraine would be associated with insomnia but not sleep apnea. Background Sparse research has examined migraine prevalence and sleep comorbidities in underrepresented racial and ethnic groups in the United States. Hispanic/Latino adults in the United States may be at risk for worse health outcomes due to disparities in health‐care access and socioeconomic stressors. Methods We analyzed data collected during the baseline examination (March 2008–June 2011) from the HCHS/SOL, a community‐based cohort study of self‐identified Hispanic/Latino adults in the United States. The exposure was self‐reported medical diagnosis of migraine, and primary outcomes were obstructive sleep apnea (apnea–hypopnea index ≥ 15 events/h from at‐home sleep testing) and insomnia (≥ 9 on the Women's Health Initiative Insomnia Rating Scale). Exploratory outcomes included self‐reported sleep duration, timing, sleeping pill use, and naps. We compared weighted differences in outcomes by migraine status, adjusting for age and sex in all reported models. Results Our analytical sample included HCHS/SOL participants who completed questionnaires on sleep and migraine (16,325). The mean age (standard deviation) was 41.1 (31.7) years, 52.2% identified as female, and 39.5% had a body mass index ≥ 30 kg/m2. Lifetime prevalence of migraine was 15.9% (95% confidence interval [CI]: 15.0, 16.8; 23.6% [95% CI: 22.2, 25.0] of females and 7.5% [95% CI:6.6, 8.5] of males). Those with migraine were more likely to be unemployed (50.8% vs. 36.2%) and to have a household yearly income of < $20,000 (50.9% vs. 45.5%). There was no association between migraine and obstructive sleep apnea (odds ratio [OR] 0.98 [95% CI: 0.76, 1.26]) or napping (OR 0.92 [95% CI: 0.81, 1.06]). Compared to individuals without migraine, those with migraine were more likely to have insomnia (OR = 1.87; 95% CI: 1.62, 2.15) and to use sleeping pills (OR = 2.16; 95% CI: 1.80, 2.60) in sex‐ and age‐adjusted models. Individuals with migraine also had shorter mean sleep duration (7.88 ± 2.5 h vs. 8.00 ± 2.1 h, β = −0.20; 95% CI: −0.30, −0.09) and later bedtimes (11:28 p.m. ± 5.1 h vs. 11:17 p.m. ± 4.2 h, β = 16.85; 95% CI: 3.58, 30.13; weekdays) in sex‐ and age‐adjusted models. Conclusion Self‐reported medical diagnosis of migraine is common in Hispanic/Latino adults, especially females. Migraine is not associated with obstructive sleep apnea. Consistent with non‐Hispanic/Latino populations, migraine is associated with insomnia in the HCHS/SOL. Plain Language Summary In a nationwide study of 16,000 US adults who identify as Hispanic/Latino, we studied whether having migraine is related to having sleep problems. We used a home sleep study to test for sleep apnea (a temporary halt in airflow during sleep due to muscle relaxation of the back of the throat) and a questionnaire to screen for insomnia (frequent difficulties with getting to or staying asleep). Our findings indicated that adults who reported a history of migraine were more likely to have insomnia, but not sleep apnea.